2018
DOI: 10.1515/intag-2017-0049
|View full text |Cite
|
Sign up to set email alerts
|

Radiation measurements at ICOS ecosystem stations

Abstract: Solar radiation is a key driver of energy and carbon fluxes in natural ecosystems. Radiation measurements are essential for interpreting ecosystem scale greenhouse gases and energy fluxes as well as many other observations performed at ecosystem stations of the Integrated Carbon Observation System (ICOS). We describe and explain the relevance of the radiation variables that are monitored continuously at ICOS ecosystem stations and define recommendations to perform these measurements with consistent and compara… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 41 publications
0
4
0
Order By: Relevance
“…Monthly averages of these data were lower than the monthly data used in previous ForSAFE modelling (e.g. Kronnäs et al, 2019), but comparison with modelled PAR data from SMHI (Landelius et al, 2001), and measured PAR data from the ICOS network (Carrara et al, 2018) showed that the ECLAIRE data were on the right level and that the older data (which were downscaled from a global model in a simpler way) had most likely not been adjusted enough for the effect of cloudiness.…”
Section: Climate Datamentioning
confidence: 69%
“…Monthly averages of these data were lower than the monthly data used in previous ForSAFE modelling (e.g. Kronnäs et al, 2019), but comparison with modelled PAR data from SMHI (Landelius et al, 2001), and measured PAR data from the ICOS network (Carrara et al, 2018) showed that the ECLAIRE data were on the right level and that the older data (which were downscaled from a global model in a simpler way) had most likely not been adjusted enough for the effect of cloudiness.…”
Section: Climate Datamentioning
confidence: 69%
“…To estimate fAPAR from measured below canopy PPFD we used the following calculation 65 : Where, PPFD IN is the incoming photosynthetic photon flux density at the top of the canopy, PPFD OUT is the outgoing photosynthetic photon flux density, PPFD_BC IN is the incoming photosynthetic photon flux density below the canopy. All PPFD measurements are in μmol m -2 s -1 .…”
Section: Methodsmentioning
confidence: 99%
“…Both hillsides have 11° slopes like the ICOS ecosystem station Renon (Feigenwinter et al 2010) and are exposed to the same ϕp, with a 45° solar zenith angle. However, when scaled to a unit surface and compared with what perfectly leveled sensors would measure (|ϕp| cos[45°])-as specified by ICOS protocols (Carrara et al 2018)-this geometry yields solar fluxes that are 17% greater on the grassland (|ϕp| cos[34°]), and 21% reduced on the forest (|ϕp| cos[56°]). The need to measure radiative fluxes with sensors that are aligned, not horizontally but parallel to the ecosystem surface, is easily overlooked when conflating F and ϕ.…”
Section: Comment and Replymentioning
confidence: 99%